2014
DOI: 10.1016/j.trsl.2013.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Mobilizing endogenous stem cells for retinal repair

Abstract: Irreversible vision loss is most often caused by the loss of function and subsequent death of retinal neurons, such as photoreceptor cells—the cells that initiate vision by capturing and transducing signals of light. One reason why retinal degenerative diseases are devastating is that, once retinal neurons are lost, they don't grow back. Stem cell-based cell replacement strategy for retinal degenerative diseases are leading the way in clinical trials of transplantation therapy, and the exciting findings in bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 136 publications
(147 reference statements)
0
23
0
Order By: Relevance
“…Furthermore, Wang et al [12] demonstrated that the repair effect is strongly enhanced by facilitating the migration process. This similar promoting migration to repair (PMR) effect has also been observed in many other tissues [13][14][15][16]. Until now, stem cells derived from various parts of the IVD such as the nucleus pulposus (NP), annulus fibrosus (AF), and cartilage endplate (CEP) have been isolated and characterized [17][18][19][20], whereas little is known about endogenous stem cell migration with respect to difficulties in labeling target stem cells in vivo.…”
Section: Introductionmentioning
confidence: 64%
“…Furthermore, Wang et al [12] demonstrated that the repair effect is strongly enhanced by facilitating the migration process. This similar promoting migration to repair (PMR) effect has also been observed in many other tissues [13][14][15][16]. Until now, stem cells derived from various parts of the IVD such as the nucleus pulposus (NP), annulus fibrosus (AF), and cartilage endplate (CEP) have been isolated and characterized [17][18][19][20], whereas little is known about endogenous stem cell migration with respect to difficulties in labeling target stem cells in vivo.…”
Section: Introductionmentioning
confidence: 64%
“…34 like cells is consistent with previous report that endogenous stem cells may be activated to promote their differentiation into photoreceptor cells upon the damage of the retina. 35 To characterize cell communication and gap junctions of photoreceptor-like cells, we selected specific synaptic vesicle protein Synaptophysin to label the synaptic connections between regenerated photoreceptor-like cells and adjacent neurons. 36 Immunofluorescence assay showed that synaptophysin presented a multi-layer distribution in the outer plexiform photoreceptor cells at the end and within the plexiform layer.…”
Section: Rscsmentioning
confidence: 99%
“…Thus, extensive research effort is put into the development of new therapeutic options, of which regenerative stem cell (SC)-based therapies are currently attracting much attention. However, although the induction of adult endogenous retinal SCs to regenerate lost neurons would be highly desirable, to date, the reactivation and proliferation of retinal SC in vivo is not sufficient to generate enough cells to restore visual function after widespread retinal injury or disease in the adult human eye [2,3]. Thus, the replacement of exogenously derived normal functional donor cells is an attractive alternative and a promising solution.…”
Section: Regenerative Medicine For Retinal Degenerative Diseases Has mentioning
confidence: 99%